Hydrasperman pteridosperm ovules from the Permian of China: palaeoecological and palaeobiogeographic implications. (2nd December 2021) - He, Xiao-Yuan; Spencer, Alan R. T.; Wang, Shi-Jun; Hilton, Jason
ABSTRACT: Hydrasperman pteridosperms (seed ferns) were widespread and diverse in Carboniferous equatorial wetlands of Euramerica, and although present in Permian equatorial wetlands in Cathaysia, little is known about their ovules (unfertilised seeds) from this phytogeographical realm. Hydrasperman ovules are recognisable from their distinctive pollen chamber organisation, but those previously noted from the Permian floras of Cathaysia are imperfectly characterised and require further study to confirm their affinity and identity. Here we document the hydrasperman ovule Conostoma cf. kestospermum from coal-balls in the early Permian aged Taiyuan Formation of North China for which preliminary findings were previously published in a Chinese language book on the coal-ball floras of China. We provide additional information on the organisation and structure of the ovules and for the first time consider their palaeoecological and palaeogeographical significance. We conclude that significant taxonomic filtering occurred in the migration of wetland plant species between Euramerica and Cathaysia in the late Pennsylvanian, with the majority of hydrasperman pteridosperms going extinct in Euramerica at the end of the Carboniferous as a result of habitat loss and climate change. The few hydrasperman genera and species that persisted into the Cathaysian flora were relicts and a minor component of Permian equatorial wetland floras.